Thaw Consolidation Characteristics of High-Ice-Content Frozen Soil Subgrade under Seasonal Temperature Boundary Conditions - YANG Gao-sheng, MAO Hai-tao, CHEN Wen-xuan, CHEN Pei-pei, LAN Xiao-ling (长江科学院院报)
[Objective] Under the influence of climate change and engineering activities, the thermodynamic stability of subgrade engineering in permafrost regions faces severe challenges. To investigate the influence of seasonal temperature boundary conditions on the thaw consolidation characteristics of frozen soil subgrade, this study modifies the three-dimensional nonlinear large-deformation melting-thaw consolidation theory. [Methods] By introducing seasonal temperature boundary conditions and using the Mohr-Coulomb criterion to describe the plastic settlement deformation of thawed soil, a three-dimensional nonlinear plastic thaw consolidation theory incorporating seasonal temperature effects was developed. The theoretical model was numerically implemented using the FLAC3D simulation platform. Taking a typical high ice-content frozen soil subgrade section of the Qinghai-Tibet Highway as the research object, the thaw consolidation evolution patterns under seasonal temperature boundary conditions were systematically analyzed. The validity of the theoretical model was verified through comparison with field-measured data. [Results] The results showed that the settlement deformation of the frozen soil subgrade exhibited a periodic variation pattern with seasonal surface temperature changes, representing the most significant characteristic of thaw consolidation under seasonal temperature boundary conditions. Due to self-weight of subgrade soil, the distribution scope of vertical effective stress expanded with time. The calculation model considering plastic deformation demonstrated higher prediction accuracy. As plastic deformation accumulated continuously during thaw consolidation, its effect could not be neglected in long-term deformation predictions for high-ice-content frozen soil engineering. Through the study of the pore water pressure distribution during the consolidation process, it was found that the pore water in the shallow thawed area of the subgrade dissipated during initial operation. In the subsequent long-term operation, the continuous development of the thaw and settlement of frozen soil subgrade primarily resulted from the dissipation of the newly thawed pore water at the thaw front. [Conclusion] The improved theoretical model proposed in this study can more reasonably describe the thaw consolidation characteristics of high-ice-content frozen soil subgrades under seasonal temperature boundary conditions, providing a critical theoretical basis for the design and maintenance of subgrade engineering in frozen soil regions.